Left-Sided Amyand Hernia: Report of Two Cases with Review of Literature - Al-Mayoof, Ali Farooq; Al-Ani, Bilal Hamid (European Journal of Pediatric Surgery Reports, 2014)
The presence of the vermiform appendix in an inguinal hernial sac is called “Amyand” Hernia, which is a rare condition especially in children. The authors are reporting two cases of left-sided Amyand hernia in infants presented with symptoms and signs of obstructed inguinal hernia. Emergency appendectomy and herniotomy were performed. The patients were followed up for 4 to 6 months without complications. The case histories are presented, and the conditions discussed with review of the literature.
Keywords: Amyand hernia; appendectomy; herniotomy; incidental appendectomy; acute appendicitis